A Multimodal Intervention for Children with ADHD Reduces Inequity in Health and Education Outcomes. (June 2017) - Enns, Jennifer E.; Randall, Jason R.; Smith, Mark; Chateau, Dan; Taylor, Carole; Brownell, Marni; Bolton, James M.; Burland, Elaine; Katz, Alan; Katz, Laurence Y.; Nickel, Nathan C.
Objective: To evaluate whether a multimodal intervention for children with attention-deficit hyperactivity disorder (ADHD) resulted in better long-term health and education outcomes and reduced inequity across the socioeconomic gradient. Method: We analyzed administrative data held in the Manitoba Population Research Data Repository describing recipients of a combined pharmacological/behavioural intervention for ADHD. The study cohort included children aged 5 to 17 years who visited the Manitoba Adolescent Treatment Centre's ADHD intervention service at least 3 times (2007-2012). Controls were matched on age, sex, year of ADHD diagnosis, and income quintile. We compared rates of hospital and emergency department visits, medication use and adherence, contact with child welfare services, and whether children were in their age-appropriate grade. We used concentration curves to estimate differences in outcomes between children from high- and low-income families. Results: Children who received the intervention ( n = 485) had higher rates of medication use (rate ratio [RR], 1.21; 95% CI, 1.08 to 1.36) and adherence (RR, 1.42; 95% CI, 1.03 to 1.96) and were more likely to be in their age-appropriate grade (RR, 1.33; 95% CI, 1.09 to 1.63) compared with controls ( n = 1884). The intervention was also associated with reduced inequity in these outcomes across income deciles. There was no difference in the rates of hospital or emergency department visits or contacts with child welfare services. Conclusions: A multimodal ADHD intervention was associated with increased medication use and adherence and higher academic achievement. It was also related to lower inequity across the socioeconomic gradient. These results suggest that multimodal approaches may provide more equitable health and education outcomes for children with ADHD.